Measurements of Penning-Malmberg trap patch potentials and associated performance degradation - C. J. Baker; W. Bertsche; A. Capra; C. L. Cesar; M. Charlton; A. Christensen; R. Collister; A. Cridland Mathad; S. Eriksson; A. Evans; N. Evetts; J. Fajans; et al. (Physical Review Research, 2024)
Antiprotons created by laser ionization of antihydrogen are observed to rapidly escape the ALPHA trap. Further, positron plasmas heat more quickly after the trap is illuminated by laser light for several hours. These phenomena can be caused by patch potentials—variations in the electrical potential along metal surfaces. A simple model of the effects of patch potentials explains the particle loss, and an experimental technique using trapped electrons is developed for measuring the electric field produced by the patch potentials. The model is validated by controlled experiments and simulations.